Kebijakan Pembangunan di Kota Palu: Penerapan Smart City - Reza, Fachrul; Widana, Alifa Raema (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
The implementation of the smart city concept in Indonesia is one strategy for sustainable development and optimal public services. Palu City, as a developing city in Central Sulawesi, has begun adopting smart city policies to improve the quality of life of its citizens. This article discusses the background, research methods, implementation, challenges, and recommendations related to development policies in Palu City: smart city implementation using a descriptive qualitative approach and interactive model analysis. This research is based on national literature and policy sources, as well as the results of studies related to smart city implementation in various cities in Indonesia